Diagnostic performance of magnifying blue laser imaging versus magnifying narrow-band imaging for identifying the depth of invasion of superficial esophageal squamous cell carcinoma. Issue 3 (21st July 2020) - Ueda, Tomohiro; Dohi, Osamu; Naito, Yuji; Yoshida, Takuma; Azuma, Yuka; Ishida, Tsugitaka; Matsumura, Shinya; Kitae, Hiroaki; Takayama, Shun; Mizuno, Naoki; Nakano, Takahiro; Iwai, Naoto; et al.
Summary: Identifying the depth of invasion (DOI) of superficial esophageal squamous cell carcinoma (SESCC) is crucial to determine the indication for endoscopic resection. This retrospective, single-center study aimed to evaluate the diagnostic efficacy of magnifying blue laser imaging (M-BLI) compared with white-light imaging (WLI) or magnifying narrow-band imaging (M-NBI) for identifying the DOI of SESCC. A total of 160 consecutive patients with SESCCs who underwent endoscopic submucosal dissection were enrolled in this study. Still images of the lesion were obtained using WLI, M-BLI and M-NBI prior to endoscopic submucosal dissection. Three endoscopists retrospectively evaluated the DOI using WLI according to non-magnifying findings and using M-BLI and M-NBI images according to the magnifying endoscopic classification of the Japan Esophageal Society. The diagnostic accuracy of each modality was compared using the chi-square test. The DOIs in 160 SESCCs evaluated pathologically were as follows: invasion to the epithelium or lamina propria mucosa in 130, invasion to the lamina muscularis mucosa or submucosa to a depth ≤ 200 μm in 18, and invasion to the submucosa to a depth > 200 μm in 12. The overall diagnostic accuracy rates of WLI, M-BLI, M-NBI, WLI with M-BLI (WLI + M-BLI), and WLI with M-NBI (WLI + M-NBI) were 86.9, 91.2, 90.6, 95.6 and 94.4%, respectively. Significant differences were found between WLI and WLI + M-BLI or WLI + M-NBI ( P = 0.006 and P = 0.021, respectively). The concordance of intrapapillary capillary loops between M-BLI and M-NBI was 91.2%. The kappa coefficients for interobserver variability of the three endoscopists for M-BLI and M-NBI were 0.728/0.649/0.792 and 0.729/0.666/0.791, respectively, while those for intraobserver variability were 0.919/0.746/0.778 and 0.736/0.720/0.745, respectively. Similar to M-NBI, M-BLI was useful in predicting the DOI of SESCCs.